The Influence of the Cooperative Script Model using the Gasing Method Assisted by Couple Card Media on Concept Understanding - Muh. Syihab Ikbal; Kamsinah Kamsinah; Ali Umar Dani; Nurwahidah S (Universitas Lambung Mangkurat, 2021)
This study aims to, 1) analyze the understanding of the concepts of students who are taught by the cooperative script learning model using the gasing method with the help of the media couple card class XI MIA SMAN 2 Bantaeng, 2) analyze the understanding of the physics concepts of students who are taught using conventional learning models for class XI MIA. SMAN 2 Bantaeng, and 3) analyze the differences in conceptual understanding between students taught the cooperative script learning model using the gasing method assisted by the couple card media and the conventional learning model in class XI MIA SMAN 2 Bantaeng. This type of research is quasi-experimental. The research design is The Matching Only Post-Test Control Group Design. The research population was all students of class XI MIA SMAN 2 Bantaeng. The research sample is class XI MIA 1 and class XI MIA 3. The sampling technique used is two-step matching sampling. The research instrument is a conceptual understanding test. The results showed that 1) the understanding of the concepts of students who were taught with the cooperative script learning model using the gasing method assisted by the couple card media in the experimental class was categorized as very good with an average value of 89.38; 2) understanding of the concepts of students who are taught using conventional learning models in the control class is categorized as good with an average value of 79.61; 3) there is a significant difference in conceptual understanding between students who are taught with the cooperative script learning model using the gasing method assisted by the couple card media and the conventional learning model. The research implies that the cooperative script model using the gasing method with the help of the couple card media influences students' understanding of concepts better than conventional learning models.